2021
DOI: 10.1155/2021/9969372
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Adipose-Derived Mesenchymal Stem Cell Secretome against Hepatocyte Apoptosis Induced by Liver Ischemia-Reperfusion with Partial Hepatectomy Injury

Abstract: Ischemia-reperfusion injury (IRI) is an inevitable complication of liver surgery and liver transplantation. Hepatocyte apoptosis plays a significant role in the pathological process of hepatic IRI. Adipose-derived stem cells (ADSCs) are known to repair and regenerate damaged tissues by producing bioactive factors, including cytokines, exosomes, and extracellular matrix components, which collectively form the secretome of these cells. The aim of this study was to assess the protective effects of the ADSCs secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Hsiao S T et al detected higher levels of insulin-like growth factor-1, vascular endothelial growth factor-D, and interleukin-8 in the ADSC-secretome compared with those in the secretome of other mesenchymal stromal cell populations, and the ADSC-secretome had more advantages in promoting angiogenesis [ 27 ]. Now, our study has demonstrated that the ADSC-secretome not only reduced the expression levels of alanine transaminase, aspartate transaminase, and alkaline phosphatase and had obvious therapeutic effects, but also attenuated inflammation and activated the STAT3 signaling pathway to promote liver regeneration in a model of hepatic I/R combined with partial hepatectomy [ 28 ]. In this study, we observed that the ADSC-secretome improved the liver damage in a porcine hepatic I/R and hepatectomy model by alleviating hepatocyte autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Hsiao S T et al detected higher levels of insulin-like growth factor-1, vascular endothelial growth factor-D, and interleukin-8 in the ADSC-secretome compared with those in the secretome of other mesenchymal stromal cell populations, and the ADSC-secretome had more advantages in promoting angiogenesis [ 27 ]. Now, our study has demonstrated that the ADSC-secretome not only reduced the expression levels of alanine transaminase, aspartate transaminase, and alkaline phosphatase and had obvious therapeutic effects, but also attenuated inflammation and activated the STAT3 signaling pathway to promote liver regeneration in a model of hepatic I/R combined with partial hepatectomy [ 28 ]. In this study, we observed that the ADSC-secretome improved the liver damage in a porcine hepatic I/R and hepatectomy model by alleviating hepatocyte autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Liver Injury [15][16][17][18][19][20][21][22][23][24] Cancer [25,26] Cancer Treatment Injuries [27][28][29] Heart Transplantation [30] Rotator Cuff Injury [31,32] GvHD [33] Wound Healing [34][35][36][37][38][39][40][41][42][43][44][45] Parkinson's Disease [46][47][48][49][50] Alzheimer's Disease [51][52][53][54][55] ALS [56,57] Huntington's Disease [58,59] Niemann-Pick Type C Disease [60] Ocular Injury [61] Lung Injury [62,63] Acute Osseous Injury…”
Section: Disease Model Referencementioning
confidence: 99%
“…MSCs-CM are whole ingredients (secretome) secreted by MSCs during culture; therefore, their efficacy is closer to MSCs than MSCs-exo and MSCs-EV. Jiao et al [75] indicated that MSCs-CM therapy was a viable alternative to MSCs therapy. Daan et al [76] found that MSCs-CM therapy could reduce hepatocyte apoptosis by up to 90%.…”
Section: Mscs Derivative Therapymentioning
confidence: 99%